1999
DOI: 10.1111/j.1745-4530.1999.tb00492.x
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Loss as Related to Heating Uniformity in Microwave Processing of Solid Foods

Abstract: Moisture loss due to internal evaporation and its relationship to nonuniformity of heating in microwave reheating of high moisture solid foods was studied. A simple heat and mass transfer model was developed that excluded diffusional limitations of moisture movement. Microwave absorption and some dielectric and thermal properties were measured as input parameters to the model. Effect of varying microwave penetration with moisture level and temperature was included. For smaller total moisture loss, typical for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…This result probably may be caused by the edge overheating effect. Similar results were reported by Ni et al (1999), who found that most of the moisture loss occurred from the edges due to higher temperature at these locations. Fat content of patties cooked at 360 W was higher (p<0.05) at the edges than at the center position.…”
Section: Ph Values and Compositional Propertiessupporting
confidence: 79%
See 3 more Smart Citations
“…This result probably may be caused by the edge overheating effect. Similar results were reported by Ni et al (1999), who found that most of the moisture loss occurred from the edges due to higher temperature at these locations. Fat content of patties cooked at 360 W was higher (p<0.05) at the edges than at the center position.…”
Section: Ph Values and Compositional Propertiessupporting
confidence: 79%
“…A sharp edge or corner will act as an antenna and attract more energy than the surrounding areas (Ohlsson and Bengtsson, 2001;Ohlsson and Risman, 1978). These effects are well documented in many literatures (Chamchong and Datta, 1999;Ni et al, 1999;Ohlsson et al, 1974;Zeng and Faghri, 1994). Zeng and Faghri (1994) studied thawing patterns for cylindrically-shaped tylose samples with different aspect ratios.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The behavior of the electromagnetic field inside the microwave oven is very complex; then it can be used an approximation that considers an exponential decay inside the food, the Lambert's law [6,7].…”
Section: Introductionmentioning
confidence: 99%